Implications of Cocoa Pod Storage and Temperature to the Performance of Pod Components and Seedling Growth - Ari Wibowo; Indah Anita-Sari; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2021)
Cocoa seeds are recalcitrant with some problems in their storage due to lack of dormancy period. This study aimed to find out the effect of cocoa pod storage in two different temperatures and the storage period towards seed viability and growth of the seedlings. This study applied a split-plot design with storage temperature as main plot and storage period as sub-plot. Cocoa pods of Sulawesi-1 clone were harvested and stored at 20ºC and 29ºC for 3, 7, 14, and 30 days. The stored cocoa seeds were then sown for three months. The findings showed that the storage of cocoa pods at 20ºC for 30 days causing the seed water content was 45%, the growth of the seedlings after the storage was 98.7%, and could press the pod shrinkage (1.6%). The storage of cocoa pods at 29ºC for 30 days could accelerate the reduction process by 68.2%, decreased germination of seeds upto 83.4%, and reduced the water content by 44.2%. The pod storage at 20ºC for 30 days showed a high value in some aspects such as seedling height, stem diameter, leaf area, seedling fresh weight, and shoot/root ratio. The storage of pods at 29ºC for 14 days indicated a high score in the character of germination, seedlingheight, stem diameter, and fresh weight of seedlings. The storage of pods at room temperature could be conducted for 14 days, meanwhile, at controlled temperature, it could be conducted for 30 days.